Glutaeal remodelling protocol: Volumization with hyaluronic acid and collagen biostimulation with poly‐L‐lactic acid - Gladstone Faria; Ricardo Boggio; Marcelo Bellini (Wiley, 2023)
Abstract Purpose The purpose of this study is to develop an aesthetic treatment protocol for the glutes through the combination of poly‐L‐lactic acid (PLLA) and body hyaluronic acid (HA). Patients and methods Six female patients who aimed for glutaeal harmonisation were evaluated. Patients were treated with the combined protocol of Rennova Elleva® (poly‐L‐lactic acid) and Rennova Body Shape® (HA). The results were evaluated through quantitative and ultrasonographic analyses. Results The results showed that after 45-90 days after treatment there was an increase in the glutaeal region of the treated patients. The improvement in glutaeal harmonisation was demonstrated through qualitative comparisons and analyses. Conclusion Clinical evidence from these six cases suggests that the combined use of PLLA (Rennova Elleva®) and HA (Rennova Body Shape®) offers an excellent balance between efficacy and safety, with excellent aesthetic results.